The Comparative Study of Traditonal Chinese and Thai Music wind Instruments - Shuai, Haibo; Phansue, Veera; Jamnongsarn, Surasak (Journal of Roi Kaensarn Academi, 2023)
This study focuses on the wind instruments of China and Thailand, classifying and comparing them, and delving into the similarities and differences in their structural features, principles of sound generation, and tonal characteristics. It forms the conclusion that the "Chinese and Thai wind instruments shape each other", further activating the ethnic color hidden in the culture of Chinese and Thai wind instruments.